Whole Cottonseed as an Alternative to Mitigate In Vitro Methane Emissions on Low-Quality Forage-Based Diets - Hernandez, Olegario; Juárez Sequeira, Ana Verónica; García, Elisa Mariana; Zarate García, Natalia; Uñates Pellene, Francisco Augusto; Fissolo, Hector Miguel; Coria, María Sumampa; Lopez, Agustin (MDPI, 2026)
Enteric methane (CH4) emissions from ruminants are one of the major contributors to greenhouse gas emissions (GHG) from agriculture. We hypothesized that increasing levels of whole cottonseed (WCS) in diets decreases CH4 production in ruminants fed low-quality forages without compromising feed digestibility. Dietary lipid supplementation, particularly with oilseeds such as WCS, has the potential to reduce enteric CH4 production by altering rumen fermentation pathways. This study aimed to evaluate the effects of WCS inclusion in a tropical forage-based diet on in vitro gas and CH4 production, fermentation characteristics, and in vitro dry matter digestibility (IVDMD). Five treatments were tested using guinea grass hay (GG) supplemented with 0, 12.5, 25, 37.5, and 50% of WCS (DM basis). Results after 48 h of incubation showed a quadratic response of total gas production with increasing WCS inclusion (p < 0.01), with the highest values observed at 12.5% and 25% WCS. Methane production from digested DM significantly reduced at 50% WCS inclusion (−10.66% respect to control; p = 0.02), suggesting a mitigation effect without detrimental impacts on IVDMD (p = 0.16), which remained unaffected across all treatments. No effects were found in initial or final pH (p = 0.98 and p = 0.89, respectively) or total protozoa count among treatments (p = 0.99). However, levels of 50% WCS inclusion exceed the recommended limit of fat in ruminant diets (>6% DM). Further in vivo validation trials are recommended to confirm these in vitro results and evaluate long-term impacts on animal performance and CH4 emissions. This article is a revised and expanded version of Whole cottonseed as an alternative to mitigate in vitro methane emissions on low-quality forage-based diets. Presented at the International Research Symposium on Agricultural Greenhouse Gas Mitigation. From Research to Implementation. 21–24 October 2024, Berlin, Germany.